Peningkatan Kesadaran Terhadap Hak Cipta Bagi Guru-Guru SMPN 77 Jakarta - Endang Purwaningsih; Evie Rachmawati; Irfan Islami (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
With the condition of the teachers of SMP N 77 Jakarta, they have never received legal counseling on Intellectual Property Rights (IPR) especially Copyright. Knowledge enhancement is expected to motivate teachers to build their self-awareness on IPR to improve competence and ultimately to improve their performance. The solution offered is to provide counseling and training. The method of implementing the applied activities is lecture, discussion and training, with priority on the active participation of teachers. Based on the results of community service, it can be concluded: 1) legal counseling on IPR especially copyright is able to foster awareness of intellectual property so that it is expected to motivate teachers to build awareness of themselves in terms of IPR especially copyright; 2) supporting factors, namely the high desire of teachers to increase intellectual property knowledge, especially copyright.